Effect of Micronization of Maize on Quality Characteristics of Pasta. Issue 5 (10th May 2017) - Deepa, C.; Sarabhai, Swati; Prabhasankar, P.; Hebbar, H. Umesh
Abstract : Currently, production of pasta that is either gluten‐free or having lower content of gluten, using low‐cost nonwheat cereals and legumes, is becoming increasingly popular worldwide. This is mainly done to increase the nutritional value and reduce the allergenicity of the product. The quality attributes of pasta prepared from micronized maize flour with additives such as guar gum (MPG) and a combination of guar and xanthan gum (MPGX) were compared with pasta prepared from unmicronized flour with guar gum (UMPG). The optimum cooking time for pasta in all three cases (UMPG, MPG, and MPGX) was 3 min. The cooked weight of pasta MPG and MPGX was less compared with UMPG, indicating limited water penetration during cooking. The solid loss of pasta ranged between 8 and 9.5% and was within acceptable levels (<12%). Micronization increased the firmness in MPG (3.7 N) and MPGX (4.5 N) compared with UMPG pasta (2.7 N). MPGX pasta exhibited improved texture, color, and overall acceptability compared with UMPG, and these quality attributes were also comparable to commercial wheat pasta. The study indicated that micronized maize flour with gums can be used in the preparation of maize pasta with good quality attributes.